2015
DOI: 10.1177/0164027515590424
|View full text |Cite
|
Sign up to set email alerts
|

Access to a Car and the Self-Reported Health and Mental Health of People Aged 65 and Older in Northern Ireland

Abstract: This article examines relationships between access to a car and the self-reported health and mental health of older people. The analysis is based on a sample of N=65,601 individuals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In later life, older adults’ social networks increasingly become restricted due to the onset of losses, such as physical health declines (Steptoe et al , 2013; Burholt and Scharf, 2014), mobility problems (Rosso et al , 2013) and driving cessation (Siren and Hausten, 2015; Doebler, 2016). Whilst living in a rural area is sometimes romanticised (Walsh et al , 2012) and associated with better life satisfaction (Milbourne and Doheny, 2012; Oguz et al , 2013), older people who live rurally may encounter significant disadvantages in terms of social integration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In later life, older adults’ social networks increasingly become restricted due to the onset of losses, such as physical health declines (Steptoe et al , 2013; Burholt and Scharf, 2014), mobility problems (Rosso et al , 2013) and driving cessation (Siren and Hausten, 2015; Doebler, 2016). Whilst living in a rural area is sometimes romanticised (Walsh et al , 2012) and associated with better life satisfaction (Milbourne and Doheny, 2012; Oguz et al , 2013), older people who live rurally may encounter significant disadvantages in terms of social integration.…”
Section: Introductionmentioning
confidence: 99%
“…For rural dwellers, social integration in the United Kingdom (UK) and Ireland is increasingly dependent upon car ownership (Gray, 2004; Gray et al , 2006; Ahern and Hine, 2012; Milbourne and Doheny, 2012; Shergold et al , 2012; Smith et al , 2012; Walsh et al , 2012; Zeitler and Buys, 2015). By contrast, lack of access to a car in a rural area may be a measure of deprivation, with there being an additional need to explore the value of alternative means of transport for older people (Doebler, 2016). This article, then, asks participants using a rural community transport service in western Northern Ireland to reflect upon their experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Transportation barriers due to lack of access to transportation leads to rescheduling con icts longer wait times and missed or delayed care 119 . These in turn promote poorer management of chronic illness and mental health outcomes 120 . We found that patients living in zip codes with lack of available transportation tend to experience higher incidences of ASUD risks as opposed to patients living in zip codes with access to transportation.…”
Section: Transportation Barriermentioning
confidence: 99%
“…It allows them to engage in various activities, from performing daily mundane tasks such as shopping for groceries and commuting to work, to achieving broader life goals such as engaging in one's community and traveling to new places ( 3 ). Driving is strongly associated with independence, an active lifestyle, well-being, and quality of life ( 4 , 5 ). Therefore, it is not surprising that people desire to continue to be able to drive and to maintain their driver's license for as long as possible, even in light of advancing age or changes in health status ( 3 ).…”
Section: Introductionmentioning
confidence: 99%